2011
DOI: 10.1002/sce.20460
|View full text |Cite
|
Sign up to set email alerts
|

Students' views of the nature of science: A critical review of research

Abstract: This review examines 105 empirical studies that investigate students' views of the nature of science (VNOS), effects of curricular interventions on changing students' VNOS, and relations between VNOS and demographics, majors, and learning of science. The reviewed studies can be categorized into three theoretical frameworks: the unidimension, the multidimension, and the argumentative resource frameworks. Each framework is reviewed first with regard to its theoretical foundation, methods of data collection and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(157 citation statements)
references
References 166 publications
4
140
0
13
Order By: Relevance
“…This choice of talking to students about their answers to the questionnaire was based on different research in the field of science education about the uses of surveys to gather students' and teachers' views on specific topics, such as NOS (e.g. Driver et al 1996;Lederman et al 2002;Lederman 2007;Deng et al 2011). According to Lederman et al (2002), follow-up interviews can not only help ensure the face validity of the instrument items used in surveys, but also to assess Bthe respondents' reasons for adopting those positions as well^ (Lederman et al 2002, p. 504).…”
Section: Data Collectionmentioning
confidence: 99%
“…This choice of talking to students about their answers to the questionnaire was based on different research in the field of science education about the uses of surveys to gather students' and teachers' views on specific topics, such as NOS (e.g. Driver et al 1996;Lederman et al 2002;Lederman 2007;Deng et al 2011). According to Lederman et al (2002), follow-up interviews can not only help ensure the face validity of the instrument items used in surveys, but also to assess Bthe respondents' reasons for adopting those positions as well^ (Lederman et al 2002, p. 504).…”
Section: Data Collectionmentioning
confidence: 99%
“…The literature on beliefs about science not only provides insights in students' and teachers' understandings of NOS (e.g., Brickhouse 1990;Kang et al 2005; see also Deng et al 2011;Lederman 2007) and approaches to teach about NOS (e.g., Akerson et al 2010;Khishfe and Abd-El-Khalick 2002;Lederman and Abd-El-Khalick 1998), but also thoughts about how students' NOS understanding may affect their learning in science. For example, Sadler et al (2004) noted that students' conceptualizations of NOS would influence the manner in which they interpret and evaluate conflicting evidence, thus impacting their scientific reasoning skills.…”
Section: The Role Of Beliefs About Nature Of Science For Science Learmentioning
confidence: 99%
“…Although the term ''scientific literacy'' is not well defined in the literature (Deng et al, 2011, and references therein), Durant (1993) claimed that at its simplest, scientific literacy is ''what the general public ought to know about science,'' (p. 129) while Jenkins (1994) more closely defined scientific literacy as implying ''an appreciation of the nature, aims, and general limitations of science, coupled with some understanding of the more important scientific ideas'' (p. 5345; see also Laugksch, 2000). Alternatively, the American Association for the Advancement of Science defined a scientifically literate person as someone who is familiar with the natural world, understands key concepts and principles of science, has the capacity for scientific reasoning, and is able to use scientific knowledge for personal and social purposes (AAAS Project 2061Jurecki and Wander, 2012).…”
Section: What Is Scientific Literacy?mentioning
confidence: 99%
“…No matter the definition or framework for scientific literacy, an understanding of the scientific process is considered a vital component of scientific literacy (e.g., Millar and Osborne, 1998; Abd-El-Khalick and Lederman, 2000;Lederman, 2007;Deng et al, 2011), and Driver et al (1996) stressed the personal and societal benefits of producing students who have sophisticated views of the nature of science. Importantly, Miller (2010aMiller ( , 2010bMiller ( , 2012 has clearly shown that exposure to college science courses is a strong predictor of civic scientific literacy in adults of all ages, so it is likely that all students who complete an introductory geoscience course will become more scientifically literate, regardless of pedagogy.…”
Section: What Is Scientific Literacy?mentioning
confidence: 99%
See 1 more Smart Citation